’Est bon, tout ce qui fait pétiller le feu’ - Rodegem, Francis (Afrika Focus, 1985)
Classifying proverbs and other sayings is often awkward. To consult any collection easily, the reader must be taken into account. The classification preconised here is based on a common semantic content : the basic needs of Man. Hence, some 80 stereotyped quotations taken for a coherent whole are offered here about the sentimental life of human beings. The Wisdom of people speaking 18 different languages judges in very similar manner the relation between Man and Woman. KEYWORDS : Proverb, gnomic wisdom